Investigating effects of emoji on neutral narrative text: Evidence from eye movements and perceived emotional valence. (August 2020) - Robus, Christopher M.; Hand, Christopher J.; Filik, Ruth; Pitchford, Melanie
Abstract: Digital images of faces such as emoji in virtual communication have become increasingly popular, but current research findings are inconsistent regarding their emotional effects on perceptions of text. Similarly, emoji effects on reading behaviours are largely unknown and require further examination. The present study ( N  = 41) investigated how the position and emotional valence of emoji in neutral narrative sentences influenced eye movements during reading and perceptions of sentence valence. Participants read neutral narrative sentences containing smiling or frowning emoji in sentence-initial or sentence-final positions and rated the perceived emotional valence of the sentence. Results from linear mixed-effects models demonstrated significantly longer fixations on sentence-final emoji and longer sentence reading times when emoji were in sentence-final positions. These findings are comparable to sentence 'wrap-up' effects witnessed in the processing of lexical units during sentence reading, providing new evidence towards the way readers integrate emoji into contextual processing. However, no impact of emoji valence or position on first-pass target word processing or sentence-valence ratings were found. This would refute previous suggestions that digital faces influence text valence, raising questions about reader preference for emoji or sentence sentiment, the influence of sentence formatting, and delivery/display mechanism on these effects. Highlights: Readers fixated longer on emoji positioned at the end of a sentence than the start. Centre-sentence first-pass reading was not affected by emoji position or expression. Sentences and middle-position words were re-read more when emoji were at the end. Emoji did not appear to influence readers on perceptions of sentence emotionality.